2016
DOI: 10.1007/s11248-016-9970-4
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient and inducible DNA excision in transgenic silkworms using the FLP/FRT site-specific recombination system

Abstract: Efficient and inducible recombinase-mediated DNA excision is an optimal technology for automatically deleting unwanted DNA sequences, including selection marker genes. However, this methodology has yet to be established in transgenic silkworms. To achieve efficient and inducible FLP recombinase-mediated DNA excision in transgenic silkworms, one transgenic target strain (TTS) containing an FRT-flanked silkworm cytoplasmic actin 3 gene promoter (A3)-enhanced green fluorescent protein (EGFP) expression cassette, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 61 publications
(80 reference statements)
0
9
0
Order By: Relevance
“…Further research confirmed that both pre‐blastoderm microinjection of FLP mRNA and continuous expression of FLP recombinase through sexual hybridization can increase the efficiency of the FRT ‐flanked marker gene excision in the transgenic silkworm genome (Long et al. , 2016). We also established a heat shock‐induced site‐specific marker gene excision technology in transgenic silkworms using the FLP/FRT system (Long et al.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Further research confirmed that both pre‐blastoderm microinjection of FLP mRNA and continuous expression of FLP recombinase through sexual hybridization can increase the efficiency of the FRT ‐flanked marker gene excision in the transgenic silkworm genome (Long et al. , 2016). We also established a heat shock‐induced site‐specific marker gene excision technology in transgenic silkworms using the FLP/FRT system (Long et al.…”
Section: Introductionmentioning
confidence: 89%
“…We also established a heat shock‐induced site‐specific marker gene excision technology in transgenic silkworms using the FLP/FRT system (Long et al. , 2016). In 2013, we proved that the phiC31 recombinase‐mediated cassette exchange (phiC31‐RMCE) reaction based on the phiC31/ att system could achieve the precise site‐specific integration/replacement of foreign genes at predetermined chromosome sites in the transgenic silkworm (Long et al.…”
Section: Introductionmentioning
confidence: 99%
“…G0 fertile adults were backcrossed with wild-type adults to produce G1 offspring. The G1 individuals were assessed for the expression of green fluorescent proteins under the stereomicroscope with a GFP filter (Olympus MacroViewMVX10-AUTO, Tokyo, Japan), as described previously (Long et al, 2013;Long et al, 2016).…”
Section: Germline Transformations Of Diapause Silkworm Strainsmentioning
confidence: 99%
“…[38][39][40] The copy number and chromosomal insertion sites of the transgene constructs were determined by Southern blot and inverse PCR, respectively, as described previously with some improvements. 38,39,41 Full experimental procedures are provided in the supplemental information.…”
Section: Design and Construction Of Piggybac-derived Vectorsmentioning
confidence: 99%